2020
DOI: 10.3390/nu12113562
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Dehydration in Nursing Home Residents

Abstract: Chronic dehydration mainly occurs due to insufficient fluid intake over a lengthy period of time, and nursing home residents are thought to be at high risk for chronic dehydration. However, few studies have investigated chronic dehydration, and new diagnostic methods are needed. Therefore, in this study, we aimed to identify risk factors for chronic dehydration by measuring serum osmolality in nursing home residents and also to evaluate whether examining the inferior vena cava (IVC) and determining the IVC col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
3

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 54 publications
0
12
0
3
Order By: Relevance
“…In a previous study, we observed the cross-sectional association between chronic dehydration and dementia in nursing home residents. 2 On the one hand, dementia may increase the risk of dehydration owing to insufficient fluid intake, decreased physical function, dysphagia, comorbidities, and polypharmacy. On the other, dehydration may lead to lower cognitive function because lower hydration status has been found to be related to decreased attention and processing speed.…”
Section: Association Of Dehydration With Development Of Dementia Among Non-demented Geriatric Outpatientsmentioning
confidence: 99%
See 3 more Smart Citations
“…In a previous study, we observed the cross-sectional association between chronic dehydration and dementia in nursing home residents. 2 On the one hand, dementia may increase the risk of dehydration owing to insufficient fluid intake, decreased physical function, dysphagia, comorbidities, and polypharmacy. On the other, dehydration may lead to lower cognitive function because lower hydration status has been found to be related to decreased attention and processing speed.…”
Section: Association Of Dehydration With Development Of Dementia Among Non-demented Geriatric Outpatientsmentioning
confidence: 99%
“…Masaaki Nagae, 1 Hiroyuki Umegaki, 1 Yusuke Suzuki, 2 Hitoshi Komiya, 1 Kazuhisa Watanabe, 1 Yosuke Yamada 1 and Masafumi Kuzuya 1 1 Department of Community Healthcare and Geriatrics, Nagoya University Graduate School of Medicine, Nagoya, Japan 2 Center for Community Liaison and Patient Consultations, Nagoya University Hospital, Nagoya, Japan Dear Editor, The COVID-19 pandemic has had a devastating impact on seniors worldwide. Prevention measures such as socialdistancing have resulted in isolation, depression and reduced activity.…”
Section: Disclosure Statementmentioning
confidence: 99%
See 2 more Smart Citations
“…La deshidratación aguda es una pérdida de agua y sodio, a menudo causada por vómitos, diarrea o sudoración, entre otros, y puede ser experimentada por personas de todas las edades. Por el contrario, la deshidratación crónica se debe a una ingesta insuficiente de líquidos durante un período prolongado, causando un déficit de líquidos principalmente en el compartimento del líquido intracelular debido al aumento de la osmolalidad(8). Esta puede empezar en ausencia de enfermedad aguda y es el tipo más común en las personas mayores institucionalizadas(9).En esta población, la prevalencia de la deshidratación puede oscilar entre el 12 % y el 50 % (10-12).…”
unclassified